Time Course of Change in Blood Pressure from Sodium Reduction and the DASH Diet - Juraschek, Stephen P (Hypertension, 2017)
Both sodium reduction and the DASH diet lower blood pressure (BP); however, the patterns of their effects on BP over time are unknown. In the DASH-Sodium trial, adults with pre-/stage 1 hypertension, not using antihypertensive medications, were randomly assigned to either a typical American diet (control) or DASH. Within their assigned diet, participants randomly ate each of three sodium levels (50, 100, and 150 mmol/d, at 2100 kcal) in 4-week periods. BP was measured weekly over 12wks; 412 participants enrolled (57% women, 57% black, mean age 48years, mean SBP/DBP 135/86 mmHg). For those assigned control, there was no change in SBP/DBP between weeks 1 and 4 on the high sodium diet (weekly change −0.04/0.06 mmHg/week) versus a progressive decline in BP on the low sodium diet (−0.94/−0.70 mmHg/week; P-interactions between time and sodium <0.001 for SBP and DBP). For those assigned DASH, SBP/DBP changed −0.60/−0.16 mmHg/week on the high versus −0.42/−0.54 mmHg/week on the low sodium diet (P-interactions between time and sodium=0.56 for SBP and 0.10 for DBP). When comparing DASH to control, DASH changed SBP/DBP by −4.36/−1.07 mmHg after 1wk, which accounted for most of the effect observed, with no significant difference in weekly rates of change for either SBP (P-interaction=0.97) or DBP (P-interaction=0.70). In the context of a typical American diet, a low sodium diet reduced BP without plateau, suggesting that the full effects of sodium reduction are not completely achieved by 4wks. In contrast, compared with control, DASH lowers BP within a week without further effect thereafter.